Contact Lens Care among Teenage Students in Italy: A Cross-Sectional Study. (3rd May 2016) - Abbouda, Alessandro; Restivo, Lucia; Bruscolini, Alice; Pirraglia, Maria Pia; De Marco, Federica; La Cava, Maurizio; Pivetti Pezzi, Paola
ABSTRACT: Aim : To assess the attitude and practice of contact lens (CL) wearers among teenage school students and to evaluate how much the teenagers adhere to the CL care procedures according to the proper care of CL guidelines. Methods : A cross-sectional descriptive study of Italian teenagers from high schools in Rome who wear CL. We inquired about the different aspects of CL care through a questionnaire. Results : We investigated 3, 106 students from high schools in Rome (2% of all Roman high school students), 293 of whom wore CL (9%); 151 (52%) of participants responded, 42 (27.8%) male and 109 (72.8%) female. The mean age was 16.4 ± 1.6 years. 79.5% of students were daily users. 45.7% wore CL more than nine hours/day. 87.4% wore soft CL. 33.1% wore disposable CL; 7.9% weekly CL, 55% monthly CL. Thirty-four percent wore disposable lenses twice or more. 14.5% of students did not wash their hands before handling CL and 52.3% wore CL after it had fallen in the sink. 39.7% rubbed and cleaned CL before storing it. 10% used expired lens care solutions. Only 31.1% changed CL cases every three months. 38.4% wore CL in a swimming pool. 61.6% were having problems: redness (13.9%), itching (7.9%), and foreign body sensation (29.1%). Conclusion : Many students don't properly care for their CL. Education regarding proper care and management of CL among users is advised in view of frequency of symptoms and complications reported.